Increasing diversity through goal-setting in corporate social responsibility reporting. Issue 5 (20th June 2016) - Motel, Laura
Abstract : Purpose: The purpose of this paper is to evaluate the effect of goal-setting theory in remediating workplace demographic representation inequality. Design/methodology/approach: This study evaluates the effect of goal-setting theory in Fortune 100 companies' corporate social reporting (CSR) on year-over-prior change in diversity representation using t -tests and independent, repeated measures ANOVA. Findings: Reporting companies significantly outperformed the population in minority and female leadership increases. Companies using specific goals and relevant feedback facilitated better outcomes for minority and female leaders, respectively. Research limitations/implications: Dichotomous coding was employed. Qualitative coding over multiple years is suggested for future research. CSR reporting is voluntary, unaudited, and inconsistent. Comparing outcomes for organizations with mandatory reporting or diversity quotas would provide interesting future comparatives. Despite the limitations, this research demonstrates the benefits of goal-setting theory on social outcomes. Practical implications: Companies transparently publishing goals, feedback, and metrics lead the way to multicultural environments. Additionally, investors use social responsibility in investment decision making. The Securities and Exchange Commission should incorporate non-financial requirements into existent reporting subject to audit, consistent presentation, and public availability. Organizations should disclose diversity goals and outcomes whether the company aspires to genuinely promote greater representation or avoid greater regulation. Reporting transparency and articulation of specific, measureable goals and feedback are encouraged for non-financial metrics. Originality/value: Significant research investigates why inequality exists in organizations yet little addresses how to reduce the problem. Pioneer studies in applying goal-setting to diversity show promise. Research exploring the dark side of goal-setting is rapidly emerging. This research pursues the "light side" of goal-setting to evaluate use on social business issues, specifically, increasing diverse representation.